The effectiveness of problem-based teaching module training to increase elementary teacher motivation - Aprilia Tina Lidyasari; Sekar Purbarini Kawuryan; Yoppy Wahyu Purnomo; Faturrohman Faturrohman; Setiawan Edi Wibowo; Albi Anggito; Poh Wanyi; Augusto da Comte (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2023)
Literacy Teaching modules are an essential learning element in the independent curriculum. However, many SD Negeri Percobaan 04 Wates teachers are less motivated to develop it because they lack assistance creating their teaching modules. Based on this, the purpose of this study is to see the effectiveness of problem-based teaching module training in the independent curriculum in increasing the motivation of elementary school teachers. The training participants were 25 elementary school teachers who were SDN Percobaan 4 Wates members. Theoretical material and practical assistance were carried out in the Kapanewon Kulonprogo area. The implementation of the activity will be reflected through an evaluation of the participant's understanding of the material in terms of performance, work results, and motivation scale of the training participants. The offline training was held at the UNY Wates Campus Hall offline and online through the Zoom meeting application. This study used a pre-experiment research design with a one-group pretest-posttest design model. Data collection was carried out using a teacher motivation scale. The data analysis technique used was the Wilcoxon Test to determine the effect of training on the motivation of primary school teachers. to assess the impact of exercise on elementary school teachers' motivation. Implementing this training based on the pre-post questionnaire increased pretest and post-test results. The Wilcoxon test results significantly affected teacher motivation before and after providing problem-based teaching module training for elementary school teachers in Kulonprogo Regency, Yogyakarta Special Region. Efektivitas pelatihan modul pengajaran berbasis masalah untuk meningkatkan motivasi guru sekolah dasar Modul ajar merupakan salah satu elemen penting dalam pembelajaran di kurikulum merdeka. Namun, masih banyak guru di SD Negeri Percobaan 04 Wates yang kurang termotivasi dalam mengembangkannya karena kurang mendapatkan pendampingan untuk membuat modul ajarnya sendiri. Berdasar pada hal tersebut maka tujuan dalam penelitian ini adalah melihat efektivitas pelatihan modul ajar berbasis masalah dalam kurikulum merdeka dalam meningkatkan motivasi guru sekolah dasar. Peserta pelatihan berjumlah 25 guru sekolah dasar yang tergabung pada SDN Percobaan 4 Wates. Materi teori dan pendampingan praktik dilaksanakan di wilayah Kapanewon Kulonprogo. Pelaksanaan kegiatan akan direfleksikan melalui evaluasi pemahaman peserta terhadap materi, ditinjau dari unjuk kerja, hasil karya, dan skala motivasi peserta pelatihan. Pelatihan secara luring dilaksanakan di Aula UNY Kampus Wates secara luring dan daring melalui aplikasi zoom meeting. Penelitian ini menggunakan desain penelitian pre-eksperimen dengan model one group pretest-posttest design. Pengumpulan data dilakukan dengan menggunakan skala motivasi guru. Teknik analisis data yang digunakan adalah Test Wilcoxon untuk mengetahui pengaruh pelatihan terhadap motivasi guru SD. Adapun hasil dari pelaksanaan pelatihan ini berdasarkan angket pre-post diperoleh hasil terjadi peningkatan hasil pretest dan posttest. Sedangkan hasil uji Wilcoxon menunjukkkan bahwa terdapat pengaruh yang signifikan pada motivasi guru sebelum dan setelah pemberian pelatihan modul ajar berbasis masalah pada para guru SD di Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta.